2011
DOI: 10.5812/kowsar.22287523.1529
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lumbar discectomy on disability and depression in patients with chronic low back pain

Abstract: Background:Back pain is one of the most prevalent health problems for which physicians are consulted. Back pain has many economic impacts, such as sickness absences and long-term disability. The prevalence of major depression in patients with chronic low back pain is approximately 3 to 4 times greater than the prevalence rate reported in the general population.Objectives:This study was designed to evaluate the depression and disability improvement after lumbar discectomy compared with presurgery levels in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…(1). The authors demonstrated the beneficial role of surgery in chronic back pain for patients with disability and depression.…”
Section: Dear Editormentioning
confidence: 98%
“…(1). The authors demonstrated the beneficial role of surgery in chronic back pain for patients with disability and depression.…”
Section: Dear Editormentioning
confidence: 98%
“…The authors have concluded that the depression and disability scores of patients with chronic herniated discs before lumbar discectomy significantly decreased after surgery (2). It has long been known that patients with psychological comorbidities often incur long-term disability from low-back pain (3,4).…”
Section: Dear Editormentioning
confidence: 99%
“…The answer can be found in a paper by Farzanegan et al (1) reporting the study where 148 patients with LBP and depression had laminectomy procedure. This study broadens an understanding of the need to improve the patient-oriented assessment of spinal surgery outcomes, especially in the range of function state and depressive symptoms.…”
mentioning
confidence: 95%